Simulation of the future evolution track of “production–living–ecological” space in a coastal city based on multimodel coupling and wetland protection scenarios - Yitong Yin; Rongjin Yang; Zechen Song; Yuying Zhang; Yanrong Lu; Le Zhang; Meiying Sun; Xiuhong Li (Geography and Sustainability)
Coastal cities hold a special position in the fields of production, living, and ecological research because of their unique wetland resource advantages. However, with global urbanization and rapid economic development, conflicts among production, living and ecological land are prevalent in coastal cities in the process of maintaining sustainable wetland resources and further developing the social economy. By establishing an SD-PLUS-CCD coupling model, this paper analysed the evolution characteristics and driving mechanism of the production–living–ecological space (PLES) and the effects of wetland protection (WLP) on promoting or inhibiting the coordinated development of the PLES in Dongying city during 2005–2060. The results show that (1) from 2005 to 2020, the increase in urban population resulted in a significant transfer of arable land and a reduction of 914 km2 in production space (PS); (2) from 2020 to 2060, under the WLP scenario, the conversion of wetland ecological space will reduce the PS and living space (LS) by 193.92 km2 and 107.14 km2, respectively, and increase the ecological space (ES) by 327.52 km2; and (3) wetland protection has an inhibitory effect on the coordinated development of PLES in the study area, and the total proportion of noncoordinated areas of PE and living–ecological space will continue to increase during the simulation period. This paper provides a solid theoretical support for the sustainable management and protection of wetlands in coastal cities and possible PLES conflict patterns and provides a scientific basis for future territorial spatial planning and policy balance analysis.